DIAGNOSIS OF CHILDHOOD CARIES: CLINICAL EVALUATION AND COMPLEMENTARY METHODS - Lopez, Andres Santiago Quizhpi; Carvalho, Camila Nunes; de Souza, Geovanna Maria Ramos Porto; Benevides, Swelen Silva Cysne; da Silva, Leandro Stefanini; Rosa, Yuri Antônio Bolognani; Santos, Matheus Prates; Prates, Bruna Queiroz da Silva; Alves, Amanda Cypriano (Seven Editora, 2026)
Dental caries is the most prevalent oral condition in childhood, with significant repercussions on general health and child development. The contemporary understanding of the health-disease process requires that the diagnosis of caries go beyond the simple identification of the lesion, incorporating the analysis of biological, behavioral, and socioeconomic factors. This chapter presents a narrative review of recent literature on the diagnosis of childhood caries, addressing clinical evaluation and the main complementary methods available. The limitations of traditional indices and the relevance of more sensitive systems, such as the ICDAS II, for the early detection of lesions are discussed. Additionally, the importance of risk assessment is emphasized, including systemic factors such as vitamin D deficiency, salivary characteristics, microbiological profile, and dietary habits. It is concluded that a multidimensional diagnostic approach is essential for individualized therapeutic planning and for the promotion of effective preventive strategies in pediatric dentistry. DOI: https://doi.org/10.56238/sevened2026.003-004